Outcomes of Ixazomib Treatment in Relapsed and Refractory Multiple Myeloma: Insights from Croatian Cooperative Group for Hematologic Diseases (KROHEM) - Josip Batinić; Barbara Dreta; Goran Rinčić; Antonia Mrdeža; Karla Mišura Jakobac; Delfa Radić Krišto; Milan Vujčić; Mario Piršić; Željko Jonjić; Vlatka Periša; Jasminka Sinčić Petričević; Božena Coha; et al. (Medicina)
Background and Objectives: Ixazomib, used in combination with lenalidomide and dexamethasone (IRd), has shown efficacy in clinical trials for relapsed/refractory multiple myeloma (RRMM). Materials and Methods: This study evaluates the real-world effectiveness and safety of IRd in Croatian RRMM patients. A retrospective analysis was conducted on 164 RRMM patients treated with ixazomib at nine Croatian haematology centres from November 2016 to February 2023. Data on patient demographics, treatment regimens, and outcomes were collected and analysed using Kaplan–Meier survival curves and Cox proportional hazards models in R. The median age at ixazomib initiation was 66 years (range 40–91). Results: The overall response rate (ORR) was 65.8%, with 42% of patients achieving a very good partial response (VGPR) or better. The median progression-free survival (PFS) was 15.4 months, while median overall survival (OS) was 28.2 months. Hematologic toxicities included anaemia (53%), neutropenia (50%), and thrombocytopenia (45%). Infective complications, primarily COVID-19 and pneumonia, were reported in 38% of patients. The safety profile was consistent with previous studies, indicating manageable adverse events. Ixazomib-based therapy is effective and well tolerated in a real-world Croatian RRMM population. Conclusions: The findings align with clinical trial results, demonstrating the applicability of ixazomib in routine clinical practice. Further studies are needed to optimise treatment sequencing and improve patient outcomes.